MANAGEMENT OF ANORECTAL DISORDER W.S.R. TO HERBO MINERAL PREPARATION - shukl, Govind sahay; Goyal, Manisha; Agarwal, Rajaram (International Research Journal of Ayurveda & Yoga, 2024)
Āyurveda is an age old science of health which emphasize on the health than to cure disease. So, nowadays people are coming back to the nature from synthetics, hence, the Āyurveda will be the future medicinal science of the world, not only the India. In the era of fast food, there is change or irregularity in diet and diet timings and also sedentary life style. In addition to change in diet and life style, one is always under tremendous mental stress. All these causes disturb in digestive system which results into many diseases amongst them ano-rectal disorder constitute an important group. Herbomineral preparations are considered in ayurveda as Rasausadhis which are appreciated for their smaller dosages, quicker effectiveness, long durability etc. Thus the Herbomineral preparations play an important and major role in curing the ailing human beings. Many of these types of preparations are used to treat anorectal diseases like kasisadi tail, ghrita, arshkuthar rasa, abhayadi modak etc. This article is an attempt to highlight importance and mode of action of the Herbomineral preparations in anorectal disease like piles, fistula, fissure in ano etc.